Evaluasi Pentanahan Terhadap Sambaran Petir Pada SUTT 70 kV Menggunakan Electro Magnetic Transient Program (EMTP) - Sigit Setya Wiwaha; Rohmanita Duanaputri; Sigi Syah Wibowo; Adil Prasetyo; Sri Wahyuni Dali (Elposys: Jurnal Sistem Kelistrikan, 2021)
The transmission system is a system that often experiences lightning strikes and can cause back flashover (BFO) if there is a direct strike on the ground wire or on the tower. Lightning strikes can also cause touch voltage and step voltage hazards when lightning strikes the ground surface. Grounding is a safety device that functions to protect equipment, systems, humans and other living beings from electrical surges, especially lightning strikes. The grounding resistance value on the tower must be made as small as possible so as not to cause high tower voltage which can ultimately disrupt the transmission system. The grounding resistance limit according to PUIL 2000 is no more than or equal to 5 Ohms. This study aims to evaluate how feasible the tower and its protective devices are on the tower, including grounding and arresters in the event of a lightning strike. By collecting data, calculating tower voltage and simulating lightning overvoltage with the ATPdraw application. From testing the tower voltage by taking a sample on a tower with the highest grounding resistance of 5.8 Ohms on tower T63, the tower voltage value was obtained at 169.94 when given a current of 20 kA, 345.6 kV when given a current of 40 kA, and 682.03 kV when given a current of 80 kA. By calculation and simulation that the tower voltage value does not cause Back flashover (BFO) so it can be categorized as safe and feasible from lightning strike interference.